Początek Ewangelii św. Mateusza (Mt 1-4) ‒ parafraza alternatywna - Krzysztof Bardski (Warszawskie Studia Teologiczne)
In this article we present the continuation of our work on an alternative paraphrase of the Gospel according to St. Matthew. The specificity of the alternative paraphrase lies in the fact that we reach for new translation solutions that we confront with the existing translations of the Bible into Polish. The purpose of the alternative paraphrase is to revive the biblical message by abandoning some common formulations in favor of idiomatic constructions referring either to the context of Judaism in the time of Jesus, or to the etymology and original meaning of expressions that over the centuries have grown theological patina, or to modern formulations that may even be considered colloquialisms.